2018
DOI: 10.1002/joc.5714
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution projection of climate change and extremity over Israel using COSMO‐CLM

Abstract: High‐resolution climate projections over Israel (about 8 km) have been obtained with the regional model COSMO‐CLM, nested into the CORDEX‐MENA simulations at 25 km resolution. This simulation provides high‐resolution spatial variability of total precipitation and precipitation intensity. Projections are presented not only in terms of average properties, but also using a subset of extreme temperature and precipitation indices from the standard Expert Team on Climate Change Detection and Indices (ETCCDI) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 65 publications
7
49
1
Order By: Relevance
“…Recently, a new study (Hochman et al, ) projected changes for the extreme temperature and precipitation indices (2041–2070), at a very high resolution (about 8 km) over the region of Israel. A pronounced increase in the mean temperature was predicted (mainly in autumn and winter), while the extreme temperature indices projected larger increase in the minimum temperature than the maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new study (Hochman et al, ) projected changes for the extreme temperature and precipitation indices (2041–2070), at a very high resolution (about 8 km) over the region of Israel. A pronounced increase in the mean temperature was predicted (mainly in autumn and winter), while the extreme temperature indices projected larger increase in the minimum temperature than the maximum.…”
Section: Discussionmentioning
confidence: 99%
“…These projected results are in agreement with the findings of Ziv et al (), who showed a reduction in observed precipitation over Israel for the period 1975–2010, though being significant only in spring. This is also in accordance with Hochman et al (), who projected seasonal precipitation decrease over Israel for the mid‐21st century (RCP4.5) of ~30–50% in spring and autumn and ~20% in winter, through dynamically downscaling to ~8 km grid spacing, using the COSMO‐CLM regional model. Furthermore, recent studies over Israel have shown that rain gauges can capture the enhancement/reduction in precipitation downwind/upwind of urban areas, respectively (Halfon et al, ; Alpert et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Larger decreases are projected for spring and autumn (27–37% reductions at the end of the century according to RCP8.5) with respect to winter precipitation (25–31%), mostly for the hydrologic basins of the Sea of Galilee (SG), the Coast (CO), and the Mountains (YA) and less for the Western Galilee (WG) (Table S3; weather regime downscaling). The stronger decrease projected for the SG, the coast and the mountains basins reinforces earlier results (Hochman et al ), which found that the WG basin would be less affected, in terms of precipitation reductions, than the other basins of Israel. Nevertheless, this is an alarming outcome, since the important aquifers of Israel are located in the above‐mentioned three hydrologic basins and the most important are the SG and the Mountains basins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This 22 study focuses on the small rockpool shrimp Palaemon elegans (Rathke 1837). P. 23 elegans is native to the Mediterranean Sea, the Black Sea, and the East Atlantic coast, 24 ranging from Norway in the north to Namibia in the south. It inhabits coastal tidepools, 25 shallow rocky areas, submerged vegetated areas, lagoons, estuaries and man-made Mańkucka, 2010;Tsurnamal, 1963).…”
Section: Introductionmentioning
confidence: 99%